Characterization of Pseudomonas aeruginosa l,d-Transpeptidases and Evaluation of Their Role in Peptidoglycan Adaptation to Biofilm Growth - Inès Hugonneau-Beaufet; Jean-Philippe Barnier; Stanislas Thiriet-Rupert; Sylvie Létoffé; Jean-Luc Mainardi; Jean-Marc Ghigo; Christophe Beloin; Michel Arthur (Microbiology Spectrum, 2023)
ABSTRACT Peptidoglycan is an essential component of the bacterial cell envelope that sustains the turgor pressure of the cytoplasm, determines cell shape, and acts as a scaffold for the anchoring of envelope polymers such as lipoproteins. The final cross-linking step of peptidoglycan polymerization is performed by classical d,d-transpeptidases belonging to the penicillin-binding protein (PBP) family and by l,d-transpeptidases (LDTs), which are dispensable for growth in most bacterial species and whose physiological functions remain elusive. In this study, we investigated the contribution of LDTs to cell envelope synthesis in Pseudomonas aeruginosa grown in planktonic and biofilm conditions. We first assigned a function to each of the three P. aeruginosa LDTs by gene inactivation in P. aeruginosa, heterospecific gene expression in Escherichia coli, and, for one of them, direct determination of its enzymatic activity. We found that the three P. aeruginosa LDTs catalyze peptidoglycan cross-linking (LdtPae1), the anchoring of lipoprotein OprI to the peptidoglycan (LdtPae2), and the hydrolysis of the resulting peptidoglycan-OprI amide bond (LdtPae3). Construction of a phylogram revealed that LDTs performing each of these three functions in various species cannot be assigned to distinct evolutionary lineages, in contrast to what has been observed with PBPs. We showed that biofilm, but not planktonic bacteria, displayed an increase proportion of peptidoglycan cross-links formed by LdtPae1 and a greater extent of OprI anchoring to peptidoglycan, which is controlled by LdtPae2 and LdtPae3. Consistently, deletion of each of the ldt genes impaired biofilm formation and potentiated the bactericidal activity of EDTA. These results indicate that LDTs contribute to the stabilization of the bacterial cell envelope and to the adaptation of peptidoglycan metabolism to growth in biofilm. IMPORTANCE Active-site cysteine LDTs form a functionally heterologous family of enzymes that contribute to the biogenesis of the bacterial cell envelope through formation of peptidoglycan cross-links and through the dynamic anchoring of lipoproteins to peptidoglycan. Here, we report the role of three P. aeruginosa LDTs that had not been previously characterized. We show that these enzymes contribute to resistance to the bactericidal activity of EDTA and to the adaptation of cell envelope polymers to conditions that prevail in biofilms. These results indicate that LDTs should be considered putative targets in the development of drug-EDTA associations for the control of biofilm-related infections.